Hubungan Pengetahuan Ibu Hamil Trimester III tentang Antenatal Care Terhadap Pelaksanaan K4 - Omiati Natalia; Nurul Hikmah Annisa (Poltekkes Kemenkes Medan, 2021)
Antenatal care is a pregnancy check to optimize the mental and physical health of pregnant women, monitor the progress of pregnancy to ensure the health of the mother and the development of the baby. Recognizing early on any abnormalities or complications that may occur during pregnancy. The purpose of this study was to determine the relationship between the knowledge of third trimester pregnant women about antenatal care to the implementation of K4. The design used in this research is descriptive correlation withapproach cross sectional. Sampling was done by purposive sampling. Data analysis with chi square. From the results of the study the majority of respondents had good knowledge as many as 42 respondents (73.7%), and the majority of respondents did K4 as many as 50 respondents (87.7%). It can be concluded that there is a correlation between the knowledge of pregnant women in the third trimester of antenatal care to the implementation of K4 (value p = 0.000). From the results of this study it is known that with high education, the knowledge that is owned will be better and affect someone in applying it to implementation.